The widespread crucifer species Cardamine flexuosa is an allotetraploid with a conserved subgenomic structure - Mandáková, Terezie; Marhold, Karol; Lysak, Martin A (The New phytologist, 2014)
The origin of Cardamine flexuosa (Wavy Bittercress) has been a conundrum for more than six decades. Here we identify its parental species, analyse its genome structure in comparison to parental genomes and describe intergenomic structural variations in C. flexuosa. Genomic in situ hybridization (GISH) and comparative chromosome painting (CCP) uncovered the parental genomes and the chromosome composition of C. flexuosa and its presumed diploid progenitors. Cardamine flexuosa is an allotetraploid (2n = 4x = 32), originating from two diploid species, Cardamine amara and Cardamine hirsuta (2n = 2x = 16). The two parental species display almost perfectly conserved chromosomal collinearity for seven out of the eight chromosomes. A 13 Mb pericentric inversion distinguishes chromosome CA1 from CH1. A comparative cytomolecular map was established for C. flexuosa by CCP/GISH. Whereas conserved chromosome collinearity between the C. amara and C. hirsuta subgenomes might have promoted intergenomic rearrangements through homeologous recombination, only one reciprocal translocation between two homeologues has occurred since the origin of C. flexuosa. The genome of C. flexuosa demonstrates that allopolyploids can maintain remarkably stable subgenomes over 10(4) -10(5) yr throughout a wide distribution range. By contrast, the rRNA genes underwent genome-specific elimination towards a diploid-like number of loci.
Keywords: Genetic Loci; Genome Size; hybridizace in situ; Cardamine flexuosa (Wavy Bittercress); polyploidy; druhová specificita; genetické lokusy; délka genomu; Genome, Plant; genom rostlinný; karyotypizace; konzervovaná sekvence; Chromosome Painting; Conserved Sequence; ribozomální DNA; Karyotyping; In Situ Hybridization; translokace genetická; intergenome translocation; Cardamine; Brassicaceae; chromozomy rostlin; Species Specificity; Chromosomes, Plant; genome collinearity; chromosome painting; GISH (genomic in situ hybridization); Diploidy; Translocation, Genetic; Polyploidy; DNA, Ribosomal; diploidie; malování chromozomů; polyploidie